Multi-scenario simulation of land use dynamics and ecological risk: a case study of the liaohe estuary national wetland reserve using PLUS-Markov and PSR models - Hu, Nanlin; Wang, Guodong; Ma, Zijun; Zhao, Meiling; Yuan, Yusong; Zhang, Tao; Chen, Qi; Meng, Jingci; Wang, Jiaying (Frontiers in Environmental Science, 2024)
The land use and land cover (LULC) pattern play a crucial role in wetland protection, especially in the context of national park development. This study focuses on modeling the LULC pattern in the Liaohe Estuary National Nature Wetland Reserve under various future scenarios. Aiming to address the lack of a multi-indicator ecological risk framework in wetland, particularly the influence of policy changes, this paper develops a long-term Pressure-State-Response ecological risk assessment model based on the characteristics of the northern wetland environment in China, combined with the simulated multi-scenario PLUS model. The LULC has changed significantly from 2000 to 2040, especially with the decline of Phragmites australis and Suaeda glauca, as well as the increase of aquiculture, urban, and oil wells. As the two most distinct vegetation types in reserve area, the area of Phragmites australis and Suaeda glauca presented decreasing trends of 59.7 ha/year and 9.0 ha/year in the Economy Development Scenario (EDS), higher than 57.3 ha/year, 8.2 ha/year in the Natural Increasing Scenario (NIS) and 35.4 ha/year, 5.8 ha/year in the Ecological Protect Scenario (EPS). From the core area to the buffer area to the outer experimental area, the slope rate of vegetation deterioration rises severely. In comparison to the scenario of EDS, the area of Aquiculture and Oil well can be lowered by 11.4 ha/year and 1.1 ha/year with the application of ecological protection measures. Besides, under three scenarios, mean ecological risks are all showing an increasing trend from 2000 to 2040. The proportion of the high and very high level of ecological risk area continually increased from 28.8% to 40.4% from 2000 to 2040, which was mainly located in the south estuary and west urban area. In addition, the ecological risk in the EDS scenario is generally higher than that in the NIS and EPS scenarios, especially in the experimental area. Among the three protected areas, the core area has a lower growth in ecological risks than the outer buffer zone and experimental zone. Aiming for the development of Liaohe Estuary National Park, these findings provide quantitative guidance for protecting and restoring natural resources.